The Impact of B-Learning Modality to Information and Communication Technology Competence of Pedagogical Student - Dung The Nguyen (Intelektual Pustaka Media Utama, 2017)
The most practical way to convince the pedagogical students see the effectiveness of Information and Communication Technology (ICT) in teaching is to put them into a rich learning environment of technology applications and show them the effect of such learning. In (Dung Nguyen The and Thanh N.T., 2017b), we have proposed ICT competence framework to evaluate ICT competence of pedagogical students in informatics specialized. Frame of this competence, including 7 competence components with 17 criteria. Based on this framework, we have studied the impact of learning in blended learning (B-learning) modality to the competence to apply ICT in teaching of preservice teacher. The results are analyzed and assessed below.